Hybrid Adhesive Hydrogel Patch Containing Genipin-Crosslinked Gelatin–Hyaluronic Acid for Future Use in Atopic Dermatitis - Nurul Ain Zawawi; Manira Maarof; Nur Izzah Md Fadilah; Daniel Looi Qi Hao; Yasuhiko Tabata; Mh Busra Fauzi (Journal of Functional Biomaterials)
Hydrogel patches have gained significant attention in wound healing applications as they are similar to hydrogel dressings due to their moisture-retentive properties, biocompatibility, and ability to promote tissue regeneration. In this study, gelatin-based hydrogels crosslinked with genipin and incorporated with hyaluronic acid (HA) were developed to enhance mechanical stability, swelling behavior, and structural integrity. Fourier transform infrared (FTIR), thermogravimetric (TGA), and energy-dispersive X-ray (EDX) analyses were conducted and confirmed successful crosslinking and good thermal stability, ensuring hydrogel durability under physiological conditions. The optimized hydrogel (GE_HA_GNP) exhibited a sufficient water vapor transmission rate (WVTR), swelling ratio, and contact angle, allowing for effective wound exudate absorption and hydration maintenance, which is essential for accelerated healing. The findings demonstrate that the crosslinked hydrogels were able to maintain a WVTR of 500 to 1500 gm−2 day−1, a contact angle of >40°, and a swelling ratio of 700–1000%. The combination of genipin as a crosslinker and the addition of HA significantly improved the mechanical properties and biocompatibility of the hydrogels, making them promising candidates for an alternative treatment for atopic dermatitis and a potential wound dress-ing. Furthermore, the hydrogel patches show potential for future drug delivery appli-cations, with further studies required to evaluate their antimicrobial properties and long-term clinical performance.